Richness and diversity of insect pollinators in various habitats around Bogani Nani Wartabone National Park, North Sulawesi, Indonesia - Roni Koneri; Meis Nangoy; Wakhid WAKHID (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Koneri R, Nangoy MJ, Wakhid. 2021. Richness and diversity of insect pollinators in various habitats around Bogani Nani Wartabone National Park, North Sulawesi, Indonesia. Biodiversitas 22: 288-297.  The pollination of plants by insects is one of the most important and essential ecosystem services in natural and agricultural landscapes and Insect pollinators play an important role in this process. This is because they help to transfer pollen from the anther to the stigma, which leads to fertilization. This study aims to analyze the richness and diversity of insect pollinators in various habitats around the Bogani Nani Wartabone National Park, Toraut, North Sulawesi. It was carried out from June to August 2020 on three types of habitats around the National Park, namely forest edges, shrubs and agricultural land. For each habitat, four plots with a size of 50 m x 25 m were made with a distance of 100 m between them. The insect pollinator observation technique used was the scan sampling method. Furthermore, data analysis was carried out on abundance, richness index, diversity index, species evenness index, dominance index and the relationship between sampling locations and environmental factors. The results showed that there were 979 insect pollinators caught at the observation point, which consisted of 60 species from 16 families and 4 orders and the most common order was Hymenoptera with 31 species. The species which were found based on their relative abundance indicated that Nomia strigata was the most abundant followed by Nomia melanderi, Apis dorsata, Ropalidia fasciata and Amegilla zonata. Furthermore, the highest abundance of insect pollinators was found in shrub habitats, while the highest species richness and diversity were found at the forest edge. Therefore, it was concluded that different types of habitat affect the richness and diversity of insect pollinator species around the Bogani Nani Wartabone National Park. In addition, this proves that the forest area of Bogani Nani Wartabone National Park generally supports the abundance, richness, and diversity of insect pollinators, which were discovered in the surrounding habitats, namely shrubs and agricultural land.